Periictal electroclinical characteristics of postictal generalized electroencephalographic suppression after generalized convulsive seizures. Issue 20 (15th May 2020) - Tang, Yingying; Xia, Wei; Yan, Bo; Zhao, Lili; An, Dongmei; Zhou, Dong
Abstract : Abstract: The aim of this study was to investigate the demographic, clinical, and electrophysiological characteristics of postictal generalized electroencephalography (EEG) suppression (PGES), thereby facilitating the recognition of PGES and providing clues regarding its risk factors, pathophysiology, and relationship with sudden unexpected death in epilepsy patients (SUDEP). We retrospectively reviewed 237 generalized convulsive seizures (GCSs) in 126 patients during long-term video-EEG (VEEG) recordings. The associations of PGES and prolonged PGES (duration >20 seconds) with person- and seizure-specific variables were evaluated independently using SPSS software. Eighty patients (63.5%, 80/126) exhibited PGES after 127 GCSs (53.6%, 127/237) with an average PGES duration of 41.31 ± 24.03 seconds. The tonic phase was significantly prolonged in patients with PGES and prolonged PGES. PGES was independently associated with ictal semiology, which was attributable to the different proportions of GCS type 1. After seizure termination, patients with PGES had a higher percentage of postictal unresponsiveness and immobility, including oropharyngeal immobility. Between prolonged and short-duration PGES, the former was more likely to phase out gradually followed by immediate body movement, whereas the latter tended to have an abrupt, evoked termination followed by delayed body movement. Prolonged tonic duration, GCS type 1, postictal unresponsiveness, and immobility were more prone to occur with PGES, which might imply that hyperactivation of inhibitory neural networks underlies the pathophysiology of PGES and subsequent SUDEP. Any form of periictal bedside care, whether it constitutes effective medical intervention or not, is advisable due to its possible contribution to the interruption of PGES. Regardless of the PGES termination pattern, the neural network resuscitation process was progressive.